2022
DOI: 10.25122/jml-2021-0180
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on chlorine dioxide as a disinfectant

Abstract: The COVID-19 pandemic has tremendously increased the production and sales of disinfectants. This study aimed to systematically review and analyze the efficacy and safety of chlorine dioxide as a disinfectant. The literature relating to the use of chlorine dioxide as a disinfectant was systematically reviewed in January 2021 using databases such as PubMed, Science Direct, and Google Scholar. Inclusion criteria were studies that investigated the use of chlorine dioxide to assess the efficacy, safety, and impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(17 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…This observation is validated with the quantification of the spin concentration, in which the presence of the radical was reduced in 83.4% when the reaction occurred at pH 8, contrasting with a depletion of 72.1% after TEMPO activation at pH 10. In this sense, the conversion yield is higher at pH 8, even if the oxidative potential of ClO is not pH-dependent [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…This observation is validated with the quantification of the spin concentration, in which the presence of the radical was reduced in 83.4% when the reaction occurred at pH 8, contrasting with a depletion of 72.1% after TEMPO activation at pH 10. In this sense, the conversion yield is higher at pH 8, even if the oxidative potential of ClO is not pH-dependent [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, chlorine components, such as chlorine and hypochlorite, present limited use due to their reactivity [ 29 , 30 , 31 ], toxicity [ 32 ] and harmful environmental impact [ 33 ]. Chlorine dioxide gas has an excellent ability for sterilization and deodorization and is harmless to humans [ 34 ]. However, it is unstable and explosive (in high concentration) [ 35 ], which limits its potential application.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative, more cost-effective method is air disinfection. Previous studies have demonstrated the efficacy of chlorine dioxide aerosol as a disinfectant in fitness centers [ 118 ], and it has also shown promising results in the disinfection of ASFV, IAV, and Mycobacterium [ 119 , 120 ]. Hence, the utilization of chlorine dioxide as a means of air pre-treatment in pig barns exhibits considerable promise.…”
Section: Introductionmentioning
confidence: 99%